2016
DOI: 10.1097/aog.0000000000001267
|View full text |Cite
|
Sign up to set email alerts
|

Committee Opinion No 652

Abstract: The U.S. Food and Drug Administration advises against the use of magnesium sulfate injections for more than 5-7 days to stop preterm labor in pregnant women. Based on this, the drug classification was changed from Category A to Category D, and the labeling was changed to include this new warning information. However, the U.S. Food and Drug Administration's change in classification addresses an unindicated and nonstandard use of magnesium sulfate in obstetric care. The American College of Obstetricians and Gyne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Magnesium sulphate is recommended for fetal neuroprotection in women at risk of preterm birth although the optimal gestational age for its use remains uncertain [ 4 , 19 ],[ [31] , [32] , [33] , [34] ]. We found that in babies randomised at 30 to <32 weeks (51% of the cohort) there were no differences between magnesium exposed and placebo groups in any white matter region, whereas in the babies randomised at 32 <34 weeks (49% of the cohort) there was higher FA in the magnesium exposed group, although this was restricted to the left inferior longitudinal fasciculus.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium sulphate is recommended for fetal neuroprotection in women at risk of preterm birth although the optimal gestational age for its use remains uncertain [ 4 , 19 ],[ [31] , [32] , [33] , [34] ]. We found that in babies randomised at 30 to <32 weeks (51% of the cohort) there were no differences between magnesium exposed and placebo groups in any white matter region, whereas in the babies randomised at 32 <34 weeks (49% of the cohort) there was higher FA in the magnesium exposed group, although this was restricted to the left inferior longitudinal fasciculus.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually recommended for neuroprotection for extremely premature fetuses (<32 weeks) and for seizure prophylaxis in patients with preeclampsia. 58 59 However, magnesium is not without risks. One major, albeit uncommon, side effect is respiratory depression.…”
Section: Be Judicious In Magnesium Sulfate Use On Labor and Deliverymentioning
confidence: 99%
“…Despite strong evidence indicating effectiveness in preventing eclampsia, MgSO 4 is ineffective in delaying preterm birth ( 32 ). Despite weak evidence, MgSO 4 is still recommended by the American College of Obstetricians and Gynecologists for short-term pregnancy prolongation (up to 48 h) to allow the administration of corticosteroids ( 33 ). In a European population-based cohort study, 35% of women with severe pre-eclampsia, eclampsia, or HELLP syndrome received MgSO 4 before delivery.…”
Section: Effects Of Mgso 4 Treatment In Pregnancymentioning
confidence: 99%